The molecular mechanism of NF-κB dysregulation across different subtypes of renal cell carcinoma - Nour Abu Jayab; Alaa Abed; Iman M. Talaat; Rifat Hamoudi (Journal of Advanced Research)
Background: The nuclear factor kappa B (NF-κB) is a critical pathway that regulates various cellular functions, including immune response, proliferation, growth, and apoptosis. Furthermore, this pathway is tightly regulated to ensure stability in the presence of immunogenic triggers or genotoxic stimuli. The lack of control of the NF-κB pathway can lead to the initiation of different diseases, mainly autoimmune diseases and cancer, including Renal cell carcinoma (RCC). RCC is the most common type of kidney cancer and is characterized by complex genetic composition and elusive molecular mechanisms. Aim of review: The current review summarizes the mechanism of NF-κB dysregulation in different subtypes of RCC and its impact on pathogenesis. Key scientific concept of review: This review highlights the prominent role of NF-κB in RCC development and progression by driving the expression of multiple genes and interplaying with different pathways, including the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway. In silico analysis of RCC cohorts and molecular studies have revealed that multiple NF-κB members and target genes are dysregulated. The dysregulation includes receptors such as TLR2, signal-transmitting members including RelA, and target genes, for instance, HIF-1α. The lack of effective regulatory mechanisms results in a constitutively active NF-κB pathway, which promotes cancer growth, migration, and survival. In this review, we comprehensively summarize the role of dysregulated NF-κB-related genes in the most common subtypes of RCC, including clear cell RCC (ccRCC), chromophobe RCC (chRCC), and papillary RCC (PRCC).